Sexuality trasmitted disearses in the context of the house wife - Storck, Marc Arthur Loureiro; Saraiva, Alexandre S.; Rodrigues, Andrezza M.; Soares, Maria Carolina C.X. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Over lhe last ten years, the epidemie profile of the patients with the Acquired Immune Deficiency Syndrome has undergone some important changes, concerning the growth of cases among hé terosexual, female, monogamous, poor and low educated population. This study aims to characterize lhe profile of the so called "housewives" from a specific area of Manaus, Stale of Amazonas, Brazil, assisted by Municipal Primary Care Program (PSF), and verify these women 's vulnerability 10 Sexually Transmitted Diseases (STD) and Aids. A quanti-qualitative research was carried ouc through the answering of a questionnaire addressed to lhose women that Jive in that specific arca and thac were regiscered in the PSF as housewives. 63 women were selecled. A questionnaire contained questions about their social and cuhural aspects, sexual practice and knowledge about STD and Aids. The results showed thal lhe women were mainly less than 40 years old. Concerning education. 57% of them had graduated from high school. When asked about the use of condom, 75% stated never or rarely using it during sexual practice. The sexual activity in the last 2 years was presenl in 94.2% of the women. Our analysis showed that 61.5% of the women started their sexual life becween the ages of 17 and 20. The mos! common sexual praclice is vaginal intercourse. Concerning STD prevention, lhe most emphasized methods were the use of condoms, sexual relalion with just one partner and the Papa Nicolau exam. They reported the television, newspaper and radio as lhe most effeclive means ofobtaining STD/ Aids informacion. When quizzed about the HIV, 23% of the women answered all the quescions correccly, 29% answered that blood donation can be a risk of infection. The housewives thac took part of this study are young, married, have low education levei and an aclive sexual life. Most of chem do not use condoms regularly. That characterizes them as vulnerable to STD and Aids. Behind these results, we suggest che creation of specific actions of sexual educalion for this group of women. Another way to conscious women about SDT/ Aids in our city could be the Municipal Family Medical Program with primary care programs.